Immobilization of carbonic anhydrase enzyme into solid support for sequestration of carbon dioxide / Siti Nadia Abdullah - Abdullah, Siti Nadia (2018)
The rapid accumulation of carbon dioxide (CO₂), one of the greenhouse gasses has led to the climate change issues. To reduce the uncontrolled CO₂ emission, there are various technologies of carbon capture. Among of the techniques, biological approach is getting attention due to the drawbacks of chemical and physical techniques. In biological approach, introduction of carbonic anhydrase (CA) enzyme enhanced the hydration reaction of CO₂. Enzyme immobilization is one of the techniques for improving enzyme stabilities, but there are limited studies of suitable carriers for CA. Thus, the objective of presence study was conducted on the biocharacterization of immobilized CA on PVDF membrane and amberlite XAD7. Based on the findings, immobilized CA onto PVDF membrane performed higher enzyme activity as compared to amberlite XAD7. The thermal stability of immobilized CA for both support materials were achieved at 60°C, which is 20°C higher than free CA. Meanwhile, pH stability of immobilized CA has also shifted to pH 10 as compared with free CA at pH 9. For kinetics study, the kinetics parameters for Km, Vm and Kcat value for immobilized CA onto PVDF membrane was 7.5 mmo1/L, 0.76 |μmol/min and 0.13 min¯¹ respectively. In carbonation process of CO₂ using immobilized CA, the time taken for a complete carbonation reaction time was 52.5s, which is faster compared to blank solution with 55.5s at enzyme optimum temperature. The enzyme accelerates the carbonation reaction up until its optimum stability. As a conclusion, PVDF membrane was suitable as a support material for immobilized CA due to the higher of enzyme activity performance and possess better value of kinetics parameters.